Nucleoredoxin Redox Interactions Are Sensitized by Aging and Potentiated by Chronic Alcohol Consumption in the Mouse Liver - Osiris Germán Idelfonso-García; Brisa Rodope Alarcón-Sánchez; Dafne Guerrero-Escalera; Norma Arely López-Hernández; José Luis Pérez-Hernández; Ruth Pacheco-Rivera; Jesús Serrano-Luna; Osbaldo Resendis-Antonio; Erick Andrés Muciño-Olmos; Diana Ivette Aparicio-Bautista; Gustavo Basurto-Islas; Rafael Baltiérrez-Hoyos; et al. (MDPI AG, 2024)
Aging is characterized by increased reactive species, leading to redox imbalance, oxidative damage, and senescence. The adverse effects of alcohol consumption potentiate aging-associated alterations, promoting several diseases, including liver diseases. Nucleoredoxin (NXN) is a redox-sensitive enzyme that targets reactive oxygen species and regulates key cellular processes through redox protein-protein interactions. Here, we determine the effect of chronic alcohol consumption on NXN-dependent redox interactions in the liver of aged mice. We found that chronic alcohol consumption preferentially promotes the localization of NXN either into or alongside senescent cells, declines its interacting capability, and worsens the altered interaction ratio of NXN with FLII, MYD88, CAMK2A, and PFK1 proteins induced by aging. In addition, carbonylated protein and cell proliferation increased, and the ratios of collagen I and collagen III were inverted. Thus, we demonstrate an emerging phenomenon associated with altered redox homeostasis during aging, as shown by the declining capability of NXN to interact with partner proteins, which is enhanced by chronic alcohol consumption in the mouse liver. This evidence opens an attractive window to elucidate the consequences of both aging and chronic alcohol consumption on the downstream signaling pathways regulated by NXN-dependent redox-sensitive interactions.